2017
DOI: 10.22159/ajpcr.2017.v10s2.19478
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Secondary Stroke Prevention Therapies in Ischemic Stroke Patients at Teaching Hospital in Central Java Indonesia

Abstract: Objective: Patients who survive from the first stroke have risk factors to be recurrent. Based on American Heart Association/American Stroke Association and PERDOSSI (Indonesian Neurologist Association), medications which are prescribed to reduce the risk of recurrent stroke as secondary stroke prevention therapies include antiplatelet/anticoagulant as well as antihypertensive and lipid-lowering agent. Patients' adherence to the secondary stroke prevention therapies is important to reduce the recurrent stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Of the 31 studies, 12 focused on CAM usage among patients with stroke, (Lee et al, 2004;Shin et al, 2008;Shaikh et al, 2009;Chang et al, 2011;Liao et al, 2012;Pandian et al, 2012;Ali et al, 2015;Kadir et al, 2015;Chang et al, 2016;Teo et al, 2016;Weng et al, 2016;Yeh et al, 2017), 15 reported medication adherence, (De Schryver et al, 2005;Osterberg and Blaschke, 2005;Arif et al, 2007;Khan et al, 2010;Bushnell et al, 2011;Chambers et al, 2011;Kronish et al, 2013;Sjölander et al, 2013;Jiang et al, 2017;Kim et al, 2017;Wei et al, 2017;Cheiloudaki and Alexopoulos, 2019;Rohde et al, 2019;Han et al, 2020;Saade et al, 2021), and only 4 investigated CAM usage and patients' adherence to stroke medications (Johnson et al, 2012;Karuniawati et al, 2017;Alhawsawi et al, 2020;Kim et al, 2020). The study design and country settings are summarized in Table 2, Table 3, Table 4 to Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 31 studies, 12 focused on CAM usage among patients with stroke, (Lee et al, 2004;Shin et al, 2008;Shaikh et al, 2009;Chang et al, 2011;Liao et al, 2012;Pandian et al, 2012;Ali et al, 2015;Kadir et al, 2015;Chang et al, 2016;Teo et al, 2016;Weng et al, 2016;Yeh et al, 2017), 15 reported medication adherence, (De Schryver et al, 2005;Osterberg and Blaschke, 2005;Arif et al, 2007;Khan et al, 2010;Bushnell et al, 2011;Chambers et al, 2011;Kronish et al, 2013;Sjölander et al, 2013;Jiang et al, 2017;Kim et al, 2017;Wei et al, 2017;Cheiloudaki and Alexopoulos, 2019;Rohde et al, 2019;Han et al, 2020;Saade et al, 2021), and only 4 investigated CAM usage and patients' adherence to stroke medications (Johnson et al, 2012;Karuniawati et al, 2017;Alhawsawi et al, 2020;Kim et al, 2020). The study design and country settings are summarized in Table 2, Table 3, Table 4 to Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson et al assessed adherence to stroke medication and CAM use and found that 7% of non-adherent patients were using CAM as a treatment for stroke (Johnson et al, 2012). Similarly, Karuniawati et al reported that 29% were non-adherent to their medication regimen and 3.3% of them preferred to use CAM (Karuniawati et al, 2017). This study concluded that patients tended to stop taking their medication after feeling better.…”
Section: Effect Of Complementary Alternative Medicine Usage On Adhere...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other settings, medication beliefs were found to be one of the important modifiable factors associated with intentional (a conscious decision after balancing the pros and cons of a medication) and unintentional (lack of understanding or forgetfulness) non-adherence. [18][19][20][21][22] Medication beliefs in general among patients in Asia 23 and in particular to cardiovascular drugs in Indonesia 21 were reported low. The Necessity-Concern Framework emphasizes that medication beliefs consist of the necessity of drugs based on beliefs about the positive effects and concerns about the adverse consequences of taking a drug.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the prevalence of stroke increased from 7% in 2013 to 10.9% in 2018 and increased with age [5]. Based on the data basis of health research [6], number of patients who have been diagnosed stroke are 2,137,941 patients (12.1%). Stroke patients were mostly found in the age group of 45-54 y, 55-64 y, and 65-74 y [7].…”
Section: Introductionmentioning
confidence: 99%